Costs of (re)designing the organizational structure in order to improve the competitiveness of transport companies - Radivojević Nikola; Pimić Miroslav; Mitrović Nenad (Ekonomija: teorija i praksa, 2022)
The paper examines the causality between the costs of (re)designing the organizational structure of transport companies operating in the Republic of Serbia and their competitiveness. The research was conducted on the sample of 22 transport companies, applying the Granger model of causality. The research covers the period from 2006 to 2020. The primary goal of the paper is to determine whether there is a causal relationship between the costs that companies sacrifice in (re)designing the organizational structure and their competitiveness, which is in the paper expressed by the market share. The findings indicate that there is bidirectional (or feedback) causality.